Effects of Drought and Media-Reported Violence on Cattle Fever Tick Incursions - Thompson, Jada M.; Delgado, Amy H.; Hasel, Hallie S.; Bonilla, Denise L. (Frontiers in Veterinary Science, 2020)
Ectoparasites, such as cattle fever ticks, and the diseases they carry pose a risk to the global cattle population in reduced productivity and in livability. Tick infestations carry significant economic implications through losses in productivity, increased morbidity, and control costs. Cattle fever ticks were eradicated from the United States through concentrated efforts across state and federal agencies. The Cattle Fever Tick Eradication Program maintains a permanent quarantine and buffer zone along the Texas-Mexico border to monitor and control reincursions of the tick from Mexico due to movements of wildlife or stray animals. The number of apprehensions of stray livestock and changing infestation rates may be influenced by many factors including increases in violence along the border or environmental effects such as weather pattern changes, river levels, or temperature fluctuations. Using annual records of the number of cattle apprehended and infestation rates, an analysis of the effects of media-reported border violence and environmental conditions can provide a unique understanding of cattle fever tick prevention and the challenges control programs face. Results from this analysis suggest that both media-reported violence and weather changes affect the rate at which infested cattle are apprehended, and these effects differ depending on spatial and temporal factors. With continued land use changes, social unrest in endemic areas, and changing weather patterns, the efforts to control and eradicate cattle fever ticks, both in the United States and globally, is likely to be an ongoing concern.